Comparison between atom-bond connectivity indices of graphs - Das, Kinkar Ch.; Mohammed, Mohanad Ali; Gutman, Ivan; Mohd Atan, Kamel Ariffin (Faculty of Science, University of Kragujevac, 2016)
The atom-bond connectivity index ABC is a much studied degree-based graph invariant with noteworthy applications in chemistry. Few years ago, a new distance-based variant of this index, ABCGG, was introduced. We establish relations between the two ABC-indices. In particular, we determine classes of graph for which ABC is greater than (resp. equal to or less than) ABCGG.